Incorporating error shaping technique into LSF vector quantization. - Hsi-Wen Nein
This paper presents an error shaping technique for line spectrum frequency (LSF) vector quantization. The error shaping technique based on the weighted logarithm spectral distortion (WLSD) measure can be used for shaping the spectral distortion distribution of quantization error into any different curve depending on what kind of weighting function is used. However, the high computational complexity of the WLSD measure deters this error shaping technique from practical use. To solve this problem, we approximate the WLSD measure by the quadratically weighted measure or the weighted mean squared error (WMSE) measure and propose an optimal error shaping technique of LSF vector quantization. In this proposed error shaping technique, the optimal WMSE weights (i.e., the optimal weights of LSF parameters) are determined based on the theoretical analysis of the WLSD measure. Three experiments are performed to check the performance of the proposed error shaping technique. One experiment is set up by incorporating human perception into the LSF quantization and another is set up by emphasizing the human-sensitivity frequency band in lower frequency bandwidth 0-3 kHz. In the third experiment, we apply the proposed error shaping technique to the LSF quantization of a CELP coder to test how it affects the overall speech quality in an actual speech coding algorithm
Keywords: CELP coder; LPC model; LSF VQ; LSF parameters; LSF vector quantization; WLSD measure; Computational complexity; Frequency bandwidth; Human perception; Human-sensitivity frequency band; Line spectrum frequency; Optimal WMSE weights; Optimal error shaping; Quadratically weighted measure; Quantization error; Spectral distortion distribution; Speech coding algorithm; Speech quality; Weighted logarithm spectral distortion; Weighted mean squared error; Weighting function